Social Costs of Smoking in the Czech Republic - Landovská, Petra (Applied health economics and health policy, 2025)
OBJECTIVES: Smoking is an important risk factor leading to many diseases, which brings substantial healthcare costs as well as indirect costs due to decreased productivity. This article aims to quantify the social costs of smoking in the Czech Republic in 2019. METHODS: The prevalence-based, cost-of-illness approach is used, which assesses the costs as the sum of direct (healthcare) costs and indirect costs (productivity losses due to mortality and morbidity). The costs of healthcare utilization and pharmacotherapy in direct costs, and the costs of absenteeism, presenteeism, and premature mortality in indirect costs, are included. RESULTS: Total costs of smoking in the Czech Republic in 2019 are estimated as 2110.6 million EUR (0.94% of GDP). Direct costs amounted to 537.0 million EUR (2.9% of health expenditures in 2019) and indirect costs were 1573.6 million EUR, mainly driven by the costs of premature mortality (1062.5 million EUR). CONCLUSIONS: Despite the declining trend in the prevalence of smoking in the Czech Republic, the associated costs are considerable. Investments into strategies to reduce smoking continue to be needed.
Keywords: Female; lidé středního věku; presenteismus; I18; výdaje na zdravotnictví; mužské pohlaví; Smoking; Humans; Prevalence; kouření; dospělí; Absenteeism; absentérství; Czech Republic; lidé; Middle Aged; Health Care Costs; senioři; předčasná smrt; I12; ženské pohlaví; Health Expenditures; osobní újma zaviněná nemocí; náklady na zdravotní péči; Česká republika; Aged; Presenteeism; Mortality, Premature; prevalence; Cost of Illness; Adult; Male